2021
DOI: 10.3389/fphar.2021.699629
|View full text |Cite|
|
Sign up to set email alerts
|

Mcl-1 Inhibition: Managing Malignancy in Multiple Myeloma

Abstract: Multiple myeloma (MM) is a plasma cells neoplasm. The overexpression of Bcl-2 family proteins, particularly myeloid cell leukemia 1 (Mcl-1), plays a critical role in the pathogenesis of MM. The overexpression of Mcl-1 is associated with drug resistance and overall poor prognosis of MM. Thus, inhibition of the Mcl-1 protein considered as a therapeutic strategy to kill the myeloma cells. Over the last decade, the development of selective Mcl-1 inhibitors has seen remarkable advancement. This review presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 117 publications
(155 reference statements)
0
23
0
Order By: Relevance
“…A substantial portion of the genes (21%) resulted in being unfavorable prognostic markers of overall survival in at least two MM patient cohorts ( Figure 5 E). A prominent example was shown for MCL1 ( Figure 5 F), an anti-apoptotic protein highly expressed in MM with a crucial role in disease progression [ 57 ]. A further literature review identified nine genes implicated in promoting drug resistance in MM cells, including CDK6 [ 58 ], HIF1A [ 59 ], MCL1 [ 60 ], MITF [ 61 ], PPP3CA [ 62 ], PTP4A3 [ 63 ], RUNX3 [ 64 ], SGK1 [ 27 , 65 ], and USP14 [ 66 ] ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial portion of the genes (21%) resulted in being unfavorable prognostic markers of overall survival in at least two MM patient cohorts ( Figure 5 E). A prominent example was shown for MCL1 ( Figure 5 F), an anti-apoptotic protein highly expressed in MM with a crucial role in disease progression [ 57 ]. A further literature review identified nine genes implicated in promoting drug resistance in MM cells, including CDK6 [ 58 ], HIF1A [ 59 ], MCL1 [ 60 ], MITF [ 61 ], PPP3CA [ 62 ], PTP4A3 [ 63 ], RUNX3 [ 64 ], SGK1 [ 27 , 65 ], and USP14 [ 66 ] ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, MM cells in the transwell exhibited substantial changes in the regulome as compared to the monoculture. In particular, we identified a subset of genes where BMSCs induced an increase in chromatin accessibility at multiple regulatory sites, including genes known to promote drug resistance such as ABCA1 [ 56 ], SGK1 [ 27 ], and MCL1 [ 57 ]. These signature genes were enriched in biological processes related to IL6 signaling, apoptosis, angiogenesis, unfolded protein stress, and the transcription response to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The study also needs in-vitro with invivo animal studies for the con rmation of these phytochemicals as a potent inhibitor of MCL1 and PKM2 towards cancer treatment. Figure 2 the intrinsic and extrinsic processes that lead to programmed cell death in healthy mammalian cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caspase-8 and caspase-10 activate Bid, which activates Bak and Bax to induce MOMP. MOMP is a link between extrinsic and intrinsic signaling pathways [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mcl-1 dependent cancers are resistant to pan Bcl-2/Bcl-xL inhibitors (ABT-737), and venetoclax [ 186 ]. Therefore, Mcl-1 is an attractive target for MM [ 187 , 188 , 189 ]. There are several clinical trials ongoing for Mcl-1 inhibitors, for example MIK665 (also named S64315) is tested in phase I trials for refractory or relapsed lymphoma or MM patients [ 190 ].…”
Section: Glance Into the Futurementioning
confidence: 99%